Physisporinus yunnanensis sp. nov. (Polyporales, Basidiomycota) from Southern China - Cai, Jia; Zou, Lei; Wu, Xi; Zhao, Chang-Lin (Phytotaxa, 2023)
A wood-inhabiting fungal species, Physisporinus yunnanensis is proposed based on a combination of morphological features and molecular evidence. Physisporinus yunnanensis is characterized by annual, resupinate, bone-hard basidiomata with an olivaceous to black pore surface, a monomitic hyphal system, presence of hyphoid cystidia at dissepiment edge and subglobose, smooth basidiospores measuring as 4–5.5 × 3.5–5 µm, and causing a white rot. The phylogenetic analyses based on molecular data of ITS+nLSU sequences showed that P. yunnanensis is sister to P. furcatus with high support (100% BS, 100% BP, 1.00 BPP). Both morphological characteristics and molecular phylogenetic analyses confirmed the placement of the new species in Physisporinus.